1994
DOI: 10.3171/jns.1994.80.3.0491
|View full text |Cite
|
Sign up to set email alerts
|

Anaerobic glycolysis preceding white-matter destruction in experimental neonatal hydrocephalus

Abstract: The metabolic changes in neonatal hydrocephalus that lead to permanent brain injury are not clearly defined, nor is the extent to which these changes can be prevented by a cerebrospinal fluid shunt. To clarify these processes, cerebral glucose utilization was examined using [14C]2-deoxyglucose autoradiography in 1-month-old kittens, kaolin-induced hydrocephalic littermates, and hydrocephalic kittens in which a ventriculoperitoneal shunt had been inserted 10 days after kaolin injection. The hydrocephalic kitten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
33
1

Year Published

1996
1996
2010
2010

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(35 citation statements)
references
References 65 publications
1
33
1
Order By: Relevance
“…They reported that the diagnosis was made by ventriculography, but did not mention what occurred in the brain after surgery. Other reports have indicated that reconstitution of the cerebrum after shunting occurs only in the white matter [5,7,14,21,26,27]. In our case, the ventricles did not differ significantly in size at the first and forth MRI scans, but the syrinx was no longer recognizable at the fourth MRI.…”
contrasting
confidence: 49%
See 1 more Smart Citation
“…They reported that the diagnosis was made by ventriculography, but did not mention what occurred in the brain after surgery. Other reports have indicated that reconstitution of the cerebrum after shunting occurs only in the white matter [5,7,14,21,26,27]. In our case, the ventricles did not differ significantly in size at the first and forth MRI scans, but the syrinx was no longer recognizable at the fourth MRI.…”
contrasting
confidence: 49%
“…Both hydranencephaly and hydrocephalus have been known to occur concurrently with parvovirus infection [13,15]. On the other hand, experimentally induced hydrocephalus becomes apparent within 1 to 2 weeks of a kaolin injection [5,7,9,10,14,21,26,27] and the central canal dilates within 2 to 6 weeks [9,10]. As regards parvovirus infection, serum IgM and IgG levels have indicated that the infection is established within 3 days to 3 weeks after contact (Unpublished information; Nikken Bio Medical Laboratory Inc., Japan).…”
mentioning
confidence: 99%
“…The cause of cortical and brainstem changes could be a combination of direct mechanical stresses, retrograde degeneration due to axonal injury, and chronic metabolic stresses. 1,22 A prospective trial in hydrocephalic patients undergoing intracranial pressure monitoring would be needed to determine if cortical biopsy is of any value in predicting which patients will respond to shunting.…”
Section: Discussionmentioning
confidence: 99%
“…There have been many reports of animal models in which the pathological changes of brain were investigated to determine the mechanism of neuronal damages in hydrocephalus. Likely mechanisms may include mechanical distortion [3, 4, 5], ischemic effects [6, 7]and metabolism which includes impairment of the removal of waste products [8, 9, 10, 11]. …”
Section: Introductionmentioning
confidence: 99%